A physico-chemical model to study the ion density distribution in the inner coma of comet C/2016 R2 (Pan-STARRS). Issue 3 (18th December 2020) - Raghuram, Susarla; Bhardwaj, Anil; Hutsemékers, Damien; Opitom, Cyrielle; Manfroid, Jean; Jehin, Emmanuel
ABSTRACT: The recent observations show that comet C/2016 R2 (Pan-Starrs) has a unique and peculiar composition when compared with several other comets observed at 2.8 au heliocentric distance. Assuming solar resonance fluorescence is the only excitation source, the observed ionic emission intensity ratios are used to constrain the corresponding neutral abundances in this comet. We developed a physico-chemical model to study the ion density distribution in the inner coma of this comet by accounting for photon and electron impact ionization of neutrals, charge exchange and proton transfer reactions between ions and neutrals, and electron–ion thermal recombination reactions. Our calculations show that CO2 + and CO + are the major ions in the inner coma, and close to the surface of nucleus CH3 OH +, CH3 OH2 +, and O2 + are also important ions. By considering various excitation sources, we also studied the emission mechanisms of different excited states of CO +, CO2 +, N2 +, and H2 O + . We found that the photon and electron impact ionization and excitation of corresponding neutrals significantly contribute to the observed ionic emissions for radial distances smaller than 300 km and at larger distances, solar resonance fluorescence is the major excitation source. Our modelled ion emission intensity ratios are consistent with the ground-based observations. Based on the modelled emission processes, we suggest that the observed ion emission intensity ratios can be used to derive the neutral composition in the cometary coma only when the ion densities are significantly controlled by photon and photoelectron impact ionization of neutrals rather than by the ion–neutral chemistry.